Assessing Sleep Architecture With Polysomnography During Posttraumatic Amnesia After Traumatic Brain Injury: A Pilot Study. (July 2021) - Fedele, Bianca; McKenzie, Dean; Williams, Gavin; Giles, Robert; Olver, John
Background: Early-onset sleep disturbance is common following moderate to severe traumatic brain injury (TBI) and often emerges while patients are in posttraumatic amnesia (PTA). However, sleep disruptions during this subacute recovery phase are not well-defined, and research often utilizes indirect measures (actigraphy) that quantify sleep based on activity. This study aims to examine sleep macro-architecture and sleep quality directly with ambulatory polysomnography (PSG) and measure endogenous salivary melatonin levels for patients experiencing PTA following moderate to severe TBI. Method: Participants were recruited from an inpatient TBI rehabilitation unit. Nighttime PSG was administered at the patient's bedside. Two saliva specimens were collected for melatonin testing on a separate evening (24:00 and 06:00 hours) using melatonin hormone profile test kits. Results: Of 27 patients in whom PSG was recorded, the minimum required monitoring time occurred in n =17 (adherence: 63%) at a median of 37.0 days (quartile 1 [Q1] to quartile 3 [Q3]: 21.5-50.5) postinjury. Median non–rapid eye movement (NREM) and REM sleep proportions were similar to normal estimates. Slow-wave sleep was reduced and absent in 35.3% of patients. Sleep periods appeared fragmented, and median sleep efficiency was reduced (63.4%; Q1-Q3: 55.1-69.2). Median melatonin levels at both timepoints were outside the normal range of values specified for this test (from Australian Clinical Labs). Conclusion: This study reports that ambulatory PSG and salivary melatonin assessment are feasible for patients experiencing PTA and offers new insight into the extent of sleep disturbance. Further research is necessary to understand associations between PTA and sleep disturbance.